2018
DOI: 10.1002/nau.23903
|View full text |Cite
|
Sign up to set email alerts
|

International Consultation on Incontinence 2016; Executive summary: Urodynamic testing

Abstract: Aims The International Consultation on Incontinence has published an update of the recommendations for the diagnosis and management of urine incontinence (ICI2016). This manuscript summarizes the consultations committee—recommendations with regard to urodynamic assessment. Methods Expert consensus on the basis of structured evidence assessment has been the basis of the consultations publication and has been summarized by the committee for this manuscript. Results Patients that are not satisfied with their init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Urodynamic studies were performed according to International Continence Society standards [ 21 , 22 ] after the exclusion of UTI by urinalysis and culture. We evaluated the following two urodynamic parameters as essential criteria for a lack of effectiveness: maximum cystometric capacity (MCC, in the absence of sensation, the clinician decided to terminate filling in accordance with high detrusor filling pressure due to involuntary detrusor contraction/NDO) and maximum detrusor pressure (MDP) during filling cystometry [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Urodynamic studies were performed according to International Continence Society standards [ 21 , 22 ] after the exclusion of UTI by urinalysis and culture. We evaluated the following two urodynamic parameters as essential criteria for a lack of effectiveness: maximum cystometric capacity (MCC, in the absence of sensation, the clinician decided to terminate filling in accordance with high detrusor filling pressure due to involuntary detrusor contraction/NDO) and maximum detrusor pressure (MDP) during filling cystometry [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The last being a urodynamic stress test and/or leak point pressure (LPP) determination. Practice and validity of (UDS‐)LPP testing are not further discussed but are summarized, for example, in the ICI‐consultation report …”
Section: Methodsmentioning
confidence: 99%
“…There is general consensus that the CST in combination with the SUI‐S is reliable in confirming that the pathophysiology of the UI is SUI . In a review of the literature to determine the predictive value of the clinical evaluation of SUI (history, physical exam with CST) using multichannel UDS as the comparator, it was found that for the diagnosis of genuine SUI, the CST alone had sensitivity (sens:) 57%, specificity (spec:) 71%, positive predictive value (PPV) of 55% and negative predictive value (NPV) of 73% .…”
Section: Methodsmentioning
confidence: 99%
“…Patients usually have persistent storage or voiding LUTS after the surgery. VUDS provides a clear differential diagnosis to differentiate the etiology of male LUTS and may avoid unnecessary operation or overtreatment [6]. Although men with storage predominant LUTS are likely to have bladder dysfunction rather than BOO, a certain percentage of men might have BOO-related overactive bladder (OAB).…”
Section: Role Of Videourodynamic Study In the Diagnosis Of Male Lower Urinary Tract Symptomsmentioning
confidence: 99%
“…UDS can be considered as an objective measure and documents the lower urinary tract functions and dysfunctions. The results of UDS can have therapeutic consequences and may change the management strategy of LUTD [6].…”
mentioning
confidence: 99%